A 3D Morphometrical Evaluation of Brow Position After Standardized Botulinum Toxin A Treatment of the Forehead and Glabella. (14th August 2018) - Schlager, Stefan; Kostunov, Jana; Henn, Dominic; Stark, Bjoern G; Iblher, Niklas
Abstract: Background: Botulinum toxin treatment for forehead wrinkles has been extensively studied and found to be a safe and reproducible procedure. However, the effect on the position of the eyebrows, which relies on the dynamic positioning of the treated muscles, has received less attention and has not been studied with 3-dimensional (3D) technology. Objectives: The authors sought to evaluate the changes of eyebrow position after standardized botulinum toxin treatment of glabella or glabella and frontalis muscles with 3D imaging. Methods: In a prospective study, 2 groups of adult females were treated with botulinum toxin A at the glabella only (G) or at the glabella and the frontalis muscle (F/G). The brow position was measured at 5 positions with 3D photography before injection and 2 weeks, 3 months, and 6 months after injection. Results were statistically analyzed and related to patient age. Results: In the F/G group, the brow descended significantly almost across the whole brow length after 2 weeks. The descent lessened after 3 months and moved medially. No clear trend was evident in the G group. There was no significant change attributed to patient age in both groups. Conclusions: Botulinum toxin treatment of the glabella and frontalis muscle impacts the position and configuration of the eyebrow. The degree of change is affected by the amount of frontalis weakening rather than by treatment of the glabella. While age in general is not a reliable predictor, individual factors play the major role in how pronounced a change of the brow can be expected. Level of Evidence: 2: